Anti-inflammatory activities of Cinnomomum burmanni Bl - Khatib, Alfi; Mi-Yeon, Kim; Shin-Kyo, Chung (The Korean Society of Food Science and Technology, 2005)
Anti-inflammatory assay was conducted on 20 kinds of traditional Indonesian medicinal herbs using soybean lipxygenase (SLO) and hyaluronidase (HAse). C. burmanni Bl showed highest anti-inflammatory activity. Ethyl acetate fraction from methanol extract of C. burmanni Bl bark showing highest SLO inhibitory activity was isolated using silica gel-60 column chromatography. Two compounds were isolated and purified through preparative HPLC. Through analysis of UV, 1H-NMR, 13-C NMR, EI-MS and FAB+-MS, compounds 1 and 2 were identified as coumarin and 2-hydroxy cinnamaldehyde, respectively, among which 2-hydroxy cinnamaldehyde showed SLO inhibitory activity of IC50=60mikroM. Both compounds did not exhibit HAse inhibitory activity.